Angiotensin‐Converting Enzyme Inhibitors and Angiotensin II Receptor Blockers Are Associated With Improved Outcome but Do Not Prevent New‐Onset Atrial Fibrillation After Acute Myocardial Infarction. Issue 3 (March 2017) - Batra, Gorav; Lindhagen, Lars; Andell, Pontus; Erlinge, David; James, Stefan; Spaak, Jonas; Oldgren, Jonas
Abstract : Background: Treatment with renin‐angiotensin system (RAS) inhibitors might restrain the structural/electrical remodeling associated with atrial fibrillation (AF). Limited evidence exists regarding the potential benefits of RAS inhibition post‐acute myocardial infarction (AMI) in patients with AF. This study sought to assess the association between RAS inhibition and all‐cause mortality and new‐onset AF in patients with/without congestive heart failure (CHF) post‐AMI. Methods and Results: Patients hospitalized for AMI between 2006 and 2012 were identified in Swedish registries. Patients were stratified in 4 subgroups; patients with CHF and AF (n=11 489); patients with CHF without AF (n=31 676); patients with AF without CHF (n=10 066); and patients without both CHF and AF (n=59 417). Patients exposed to RAS inhibition were compared to nontreated. Three‐year risk of all‐cause mortality and new‐onset AF was assessed using adjusted Cox regression analyses. At discharge, 83 291 (73.9%) patients received RAS inhibition. RAS inhibition was associated with lower 3‐year risk of all‐cause mortality in CHF patients with AF, adjusted hazard ratio (HR) with 95% CI 0.75 (0.70–0.81), CHF patients without AF, HR 0.65 (0.60–0.69), AF patients without CHF, HR 0.82 (0.75–0.90), and in patients without CHF and AF, HR 0.76 (0.72–0.81), respectively. RAS inhibition was not associated with lower 3‐year risk of new‐onset AF in patients without AF but with/without CHF; HR 0.96 (0.84–1.10) and 1.12 (1.02–1.22), respectively. Conclusions: RAS inhibition post‐AMI was associated with lower risk of all‐cause mortality. In patients with/without CHF, RAS inhibition was not associated with lower incidence of new‐onset AF.